Evaluation of consumer acceptance of tiger prawn head flour with difference variations in soaking concentration of Rice Husk Ash Filtrate (RHAF) - Gebi Gebi; Rafitah Hasanah; Seftylia Diachanty; Ilmiani Rusdin; Andi Mismawati (Jurnal Perikanan Terpadu, 2025)
Prawn heads contain chitin about 15%-20%. This high chitin content is an obstacle in the utilization of waste that contains proteins and minerals that are still tightly bound to chitin, which is difficult for poultry digestive enzymes to digest. Therefore, it is necessary to carry out biological processing first so that the proteins and minerals bound to chitin can be broken down so that they can be digested by the poultry. Efforts to minimize chitin are by soaking the husk ash water filtrate solution. This research aims to determine consumer preference for shrimp head flour soaked in a water filtrate solution of husk ash with different concentrations. The treatments in this study were G0 (without soaking), G1 (10% FAS soaking), G2 (20% FAS soaking), and G3 (30% soaking) with a soaking time of 24 hours. The hedonic test was carried out with 30 untrained panelists, and then the data was measured using the Kruskal Wallis test, followed by the Mann-Whitney test at a confidence level of 95%. The concentration of the husk ash water filtrate solution influences consumer acceptance of tiger prawn head flour (Penaeus monodon). Based on consumer acceptance, the best treatment was G1, namely soaking FAS with a concentration of 10% for 24 hours with an appearance value of 7.77 (like very much), smell 6.43 (like), taste 5.77 (somewhat like) and texture 6.87 (like).